2005
DOI: 10.1055/s-2005-870416
|View full text |Cite
|
Sign up to set email alerts
|

Capsule Endoscopy

Abstract: IntroductionThis year's Digestive Disease Week saw the presentation of more than 80 studies focusing on capsule endoscopy (CE); this review discusses in detail the 20 most significant of these. Alongside various reports concerning technical aspects of the procedure, possible new applications have been studied, including in celiac disease. Obscure bleeding is now a consolidated indication to CE; however, prospective data on the impact of CE on clinical out− comes are still scarce. Opinions diverge on the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…15, 19 Obscure GI bleeding of presumed small-bowel origin is the principal indication for CE. 20, 21 …”
mentioning
confidence: 99%
“…15, 19 Obscure GI bleeding of presumed small-bowel origin is the principal indication for CE. 20, 21 …”
mentioning
confidence: 99%
“…The Child-Pugh classification system takes into consideration the synthetic function of the liver (albumin, INR, and bilirubin) and the clinical presentations of the portal hypertension (ascites and hepatic encephalopathy). Misra et al, Alessandro et al, Pennazio et al, and Goulas et al found that there is no association between the CTP score and the presence of PHE [ 14 , 16 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ingen-Housz further posited that the absence of light caused plants to release small quantities of carbon dioxide back into the air. 41 Longstanding prejudices against plants undoubtedly informed some of the new anxieties about respiration that emerged in the wake of this botanical research. However, in Victorian Britain, older beliefs about miasmas quickly gave way to versions of the dangerous houseplant myth that treated vegetal beings as stewards of human health and environmental harmony.…”
Section: Exploring Human-plant Relationships In the Ladies' Magazine Of Gardeningmentioning
confidence: 99%